Pengujian Tripotassium Sitrat dan Asam Sitrat Sebagai Fire Retardant Pada Kain Gorden - Kurniasih, Dewi; Ashari, Moch. Luqman; Maharani, Aditya; Santoso, Mardi; Cahyaningati, Desi; Rizal, Mochammad Choirul (Jayapangus Press, 2025)
Based on data from the Indonesian Police and Fire Department, the number of fire incidents is quite high and the most frequent fires are residential buildings. Therefore, it is necessary to conduct research related to materials that can inhibit the spread of fire. This research was conducted with the intention of determining the ability of Tripotassium Citrate in sweet potato skin and Citric Acid in inhibiting the spread of fire. The purpose of this study was to determine which material is more effective by testing and combining the dosage of each material. The method used was to conduct an experimental test on the combination of these materials in inhibiting the spread of fire. The aspects measured in this study were the mass loss and the area burned from each sample. The experimental results show that Tripotassium citrate has a function in slowing down the fire ignition stage with a mass loss ranging from 0.67 - 0.97 grams and a percentage of burned area ranging from 17.54% - 23.85%. While citric acid has a function in slowing down the fire growth stage with a mass loss ranging from 0.01 - 0.17 grams and a percentage of burned area ranging from 1.75% - 7.08%. The combination of the two materials produced results with a mass loss ranging from 0.2 - 0.8 grams and a percentage of burned area ranging from 4.27% - 14.04%. With these results, it can be concluded that Tripotassium Citrate and Citric Acid can be used as fire retardants.